Chemical Constituents of Leaves and Barks of Melicope Hookeri T.G. Hartley - Mohamad Ali, Nor Azah; Rahmani, Mawardi; Shaari, Khozirah; Mohd Ismail, Hazar Bebe; Sukari, Mohd Aspollah; Ali, Abdul Manaf; Kulip, Julias (Universiti Putra Malaysia Press, 2006)
Phytochemical investigation on the leaves and bark of Melicope hookeri T.G. Hartley (Rutaceae) has resulted in the isolation and identification of three flavonoids, ayanin, ombuin and kumatakenin, two coumarins, umbelliferone and scopoletin and p-sitosterol. The structures of these compounds were determined by detailed spectroscopic methods.